Determinan Keberlanjutan Perusahaan: Bukti Kemampuan Inovasi dan Knowledge Sharing - Annisa Wulandari; Dina Indriana; Arya Aji Aditya (Jurusan Akuntansi Politeknik Negeri Malang, 2022)
This study aimed to investigate the relationship between Knowledge Management Sharing and Green Process Innovation to Corporate Sustainable Development. This is a quantitative study using the Ordinary Least Squares regression technique. The study's population comprises companies that received awards in the Asia Sustainability Reporting Rating between 2018 and 2020. This study employed a purposive sampling technique. The analysis's findings indicate that Knowledge Management Sharing requires an antecedent to achieve Corporate Sustainable Development, while Green Process Innovation is proven to be able to encourage the creation of Corporate Sustainable Development. Abstrak Penelitian ini bertujuan untuk menguji pengaruh Knowledge Management Sharing dan Green Process Innovation terhadap Corporate Sustainable Development. Jenis penelitian adalah kuantitatif dengan metode regresi Ordinary Least Square. Populasi penelitian adalah perusahaan yang meraih penghargaan dalam Asia Sustainability Reporting Rating selama periode 2018-2020. Teknik purposive sampling digunakan peneliti. Hasil analisis menunjukkan bahwa Knowledge Management Sharing memerlukan suatu anteseden untuk mencapai Corporate Sustainable Development sedangkan Green Process Innovation terbukti mampu mendorong terciptanya Corporate Sustainable Development.